Correlação de níveis séricos de citocinas com espessura médio-intimal de carótidas em pacientes com psoríase - Lise, Michelle Larissa Zini (2015)
Introduction. Psoriasis is a common and clinically polymorphic autoimmune disease. Proinflammatory cytokines are probably involved in genesis and perpetuation of disease. The relationship of cytokines with atherogenesis in patients with psoriasis is an open theme. In this study, we aimed to compare levels of pro and anti-inflammatory cytokines and the carotid intima-media thickness (cIMT, an atherogenesis predictor) of psoriatics and controls. In parallel, we correlated such variables to each other, and both with disease activity parameters. Methods. The study was cross-sectional, and included patients with psoriasis according to traditional criteria. The cIMT was calculated by an experienced Radiologist. The cytokines IL-12p70, TNF, IL-10, IL-6, IL-1β and IL-8 were assayed by flow cytometry. The activity of psoriatic disease was evaluated by the PASI (psoriasis area and severity index) and the BSA (body surface area). Results. Sixty-five psoriatic patients and 64 controls were studied. Mean age of patients (51 years) did not differ from controls (p = 0.454). The vulgaris form was documented in 84.6% of patients. Mild disease (PASI or BSA<10) was observed in more than half of cases. Diabetes mellitus and smoking significantly predominated in cases (p<0.05), while metabolic syndrome (MS) occurred with similar frequency in both groups (p = 0.822). Median of IL-12p70, TNF, IL-1β and IL-10 were significantly lower in cases than in controls (adjusted p<0.05). An altered cIMT (≥0.9 mm) was more frequently observed in cases (p=0.039). There was no association of altered cIMT and cytokine concentrations (p> 0.05). IL-12p70 concentrations correlated with BSA and PASI (rs>0.3; p <0.05). The IL-10 concentrations were significantly lower in psoriatic with MS than without MS (p=0.006), finding not observed in controls. Conclusions. The profile of pro-inflammatory (12p70, TNF, IL-1β) and anti-inflammatory (IL-10) cytokines was reduced in our psoriatic population with predominance of mild disease. The cIMT data pointed to subclinical atherosclerosis in psoriasis. IL-12p70 concentrations correlated with active disease, whereas low concentrations of IL-10 were associated with SM in psoriatics. Further studies should clarify the cytokine-atherogenesis binomial in patients with psoriasis.